2012
DOI: 10.1038/gene.2011.89
|View full text |Cite
|
Sign up to set email alerts
|

Association of primary biliary cirrhosis with variants in the CLEC16A, SOCS1, SPIB and SIAE immunomodulatory genes

Abstract: We fine mapped two primary biliary cirrhosis (PBC) risk loci, CLEC16A (C-type lectin domain family 16 member A)–suppressor of cytokine signaling 1 (SOCS1) and Spi-B protein (SPIB) and sequenced a locus, sialic acid acetylesterase (SIAE), proposed to harbor autoimmunity-associated mutations. In all, 1450 PBC cases and 2957 healthy controls were genotyped for 84 single-nucleotide polymorphisms (SNPs) across the CLEC16A-SOCS1 and SPIB loci. All 10 exons of the SIAE gene were resequenced in 381 cases and point sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(40 citation statements)
references
References 24 publications
1
39
0
Order By: Relevance
“…In this aspect, association studies can determine whether a genetic variant is associated with PBC or not. To date, many significant susceptibility SNPs, such as CTLA4, TNF-a, STAT4, PTPN22, VDR, Clec16A, SOCS1, and SPIB, have been identified over the past two decades using candidate gene methods [28][29][30][31][32][33].…”
Section: Microsatellites and Single Nucleotide Polymorphisms (Snps)mentioning
confidence: 99%
“…In this aspect, association studies can determine whether a genetic variant is associated with PBC or not. To date, many significant susceptibility SNPs, such as CTLA4, TNF-a, STAT4, PTPN22, VDR, Clec16A, SOCS1, and SPIB, have been identified over the past two decades using candidate gene methods [28][29][30][31][32][33].…”
Section: Microsatellites and Single Nucleotide Polymorphisms (Snps)mentioning
confidence: 99%
“…It has been shown that catalytically defective heterozygous rare variants of SIAE were shown to be linked to autoimmune disorders [10,12]. These SIAE variants are associated with high odds ratios (OR) in a number of autoimmune disorders, including rheumatoid arthritis (OR 8.3), T1DM (OR 7.9), and all autoimmune disorders (OR 8.6) [10].…”
Section: Discussionmentioning
confidence: 99%
“…These SIAE variants are associated with high odds ratios (OR) in a number of autoimmune disorders, including rheumatoid arthritis (OR 8.3), T1DM (OR 7.9), and all autoimmune disorders (OR 8.6) [10]. Given that SIAE is a negative regulator of B lymphocyte signaling by acting at inhibitory receptors, a deletion of Siae gene in mice results in a defect in B-cell tolerance as evidenced by the spontaneous development of autoantibodies [13], and the risk of primary biliary cirrhosis was associated with the functionally defective SIAE variants [12], it has been suggested that SIAE plays an important role in the development of autoimmunity. SIAE has reportedly contributed to a signaling mechanism that helps set a threshold for the B-cell activation [14], suggesting that a reduction in the activity of SIAE may increase the risk for the production of autoantibodies.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the researchers concluded that rare and polymorphic variants of SIAE give rise to defects in function, which points to an association between SIAE and autoimmune disorders. Hirschfield et al (2012) sequenced the SIAE gene in 1450 PBC cases and 2957 healthy controls, and identified six cases with functional nonsynonymous SIAE mutations and functional SIAE variants that were associated with PBC risk.…”
Section: Discussionmentioning
confidence: 99%
“…Surolia et al (2010) identified distinct nonsynonymous SIAE risk variant genotypes of autoimmune diseases in individuals of European origin. Hirschfield et al(2012) revealed the potential role of functionally defective SIAE variants in the risk of primary biliary cirrhosis (PBC).These studies showed that defective SIAE variants have a strong effect on susceptibility to autoimmunity. Furthermore, studies by other investigators have confirmed the role of SLAE mutation in the development of other chronic diseases such as diabetes.…”
Section: Introductionmentioning
confidence: 99%